Isolation of Paenibacillus sp. and Variovorax sp. strains from decaying woods and characterization of their potential for cellulose deconstruction - Ghio, Silvina (2012)
Prospection of cellulose-degrading bacteria in natural environments allows the identification of novel cellulases and hemicellulases that could be useful in second-generation bioethanol production. In this work, cellulolytic bacteria were isolated from decaying native forest soils by enrichment on cellulose as sole carbon source. There was a predominance of Gram positive isolates that belonged to the phyla Proteobacteria and Firmicutes. Many primary isolates with cellulolytic activity were not pure cultures. From these consortia, isolation of pure constituents was attempted in order to test the hypothesis whether microbial consortia are needed for full degradation of complex substrates. Two isolates, CB1-2-A-5 and VG-4-A-2, were obtained as the pure constituents of CB1-2 and VG-4 consortia, respectively. Based on 16S RNA sequence, they could be classified as Variovorax paradoxus and Paenibacillus alvei. Noteworthy, only VG-4 consortium showed measurable xylan degrading capacity and signs of filter paper degradation. However, no xylan or filter paper degrading capacities were observed for the pure cultures isolated from it, suggesting that other members of this consortium were necessary for these hydrolyzing activities. Our results indicated that Paenibacillus sp. and Variovorax sp. as well as VG-4 consortium, might be a useful source of hydrolytic enzymes. Moreover, although Variovorax sp. had been previously identified in metagenomic studies of cellulolytic communities, this is the first report on the isolation and characterization of this microorganism as a cellulolytic genus.